Sustainable Business Management - Ernst, Dietmar; Sailer, Ulrich; Gabriel, Robert (UVK Verlagsgesellschaft, 2023)
This comprehensive textbook gives an insight into all relevant aspects of business administration, as they are all subject to fundamental changes due to the transformation to a more sustainable economy. It starts with the background on sustainability and the scientific classification of sustainable business administration. Next, it sheds light on the boundary conditions regarding environmental economics and social responsibility. The next section deals with management functions, from strategy and international management to change management, legal implications and HR management. The last part focuses on value creation. Here, the authors shed light on the influence of sustainability in all areas of the corporate value chain, from procurement on to production and ending with marketing and sales. Also addressed are expert functions such as environmental management or sustainable product design, which are essential in driving sustainable innovation in a dynamically changing environment.